A survey on energy consumption in fisheries, and measures to reduce CO2 emissions - Atsumi Furuya; Masahito Fukami; Harald Ellingsen; Seiichi Kagaya (European Regional Science Association (ERSA), 2011)
Japan's fish production volume in 2008 was 5.59million tons, it accounted for 4% of world's production and consisted of catch (4.40million tons) and aquaculture (1.19 million tons). For the far sea fishery, its' fishing grounds are in domestic and foreign countries' exclusive economic zone and international waters, since the total production volume of this fishery has been declining, offshore and coastal fishery have become mainly in Japan. In this study, the estimation of the energy consumptions in a kelp aquaculture and three types of fisheries, such as squid, fixed net and gill net, is done for comparison to the consumptions of fisheries in foreign countries. The result reveals that the characteristics of these fisheries' energy consumptions and the measures for reductions of energy use. Furthermore, in Minamikayabe as surveyed fishing village, the carbon dioxide balance in this village is evaluated. The carbon dioxide emissions from the energy (fuel and electricity) use and the escape Chlorofluorocarbons (CFCs) and Hydrochlorofluorocarbons (HCFCs) from freezers, refrigerators and ice manufacture machines in the village are calculated. Meanwhile, as forests and oceans are carbon dioxide sinks, it is possible to estimate the volume of carbon dioxide stored by woods and seaweed along the coast. Finally, several measures for carbon dioxide reductions are shown.
Keywords: 330